GE_GERICHTE P/12303/2022 vom 5. September 2023 - GE Cour de justice (2023)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VIOLATION DU SECRET PROFESSIONNEL(DROIT PÉNAL);FRAIS JUDICIAIRES;PLAIGNANT;ACTION RÉCURSOIRE | CPP.310; CP.321; CPP.427; CPP.420